An object–oriented mobile health system with usability features. (27th August 2012) - Escarfullet, Krystle; Moore, Cantera; Tucker, Shari; Wei, June
Mobile health (m–health) comprises the concept of utilising mobile devices to carry out the task of viewing electronic medical records, reserving medical appointments with a patient's medical provider and electronically refilling prescriptions. This paper aims at developing a m–health system to improve usability from a user's perspective. Specifically, it first developed a m–health model by logically linking characteristics of the m–health system together based on information flows. Then, the system requirements were collected by using a developed questionnaire. These requirements were structured and further in–depth analysis was conducted by using an object–oriented approach based on unified modelling language, such as use–case, sequence and analysis class diagrams. This research will be beneficial to decision makers and developers in the mobile healthcare industry.